Study of Composition and Composition of Macro Algae Habitat in the Intertidal Zone Water of Sibu Island, Nort Oba District Tidore Islands City Nort Maluku - Sukmawati Djalil; Riyadi Subur; Rina Rina; Sunarti Sunarti; Yuyun Abubakar; Aryati A. Fadel; Adi Noman Susanto; Sarni Sarni (Jurnal Biologi Tropis, 2021)
Macro algae is a part of marine plants whose whole body is called the "thallus". Macro algae are widespread in tropical and sub-tropical waters. The purpose of this study was to determine the composition of the macro algae species, the width of the micro-habitat niches, and the overlapping of the micro-habitat niches in the intertidal zone of the waters of Sibu Island, Oba Utara District, Tidore Islands City. The data was collected using survey method using belt transects and squares measuring 1x1 m2 which are placed systematically in zigzags along the tansek belt. In this study, 20 species of macro algae were found in the waters of the island of Sibu, consisting of Halimeda macroloba, Halimeada opuntia forma chordata, Halimeda incrassata, Halimeda opuntia forma renschii, Chaetamorpha sp, Eucheuma cottonii, Sargassum duplicatum, S.polycestum, Turbina ornata, T. conoides, Padina boergesenii, Dictyota dichotoma, Amphiroa fragilissima, Acanthopora spicifera, Eucheuma denticulatum, E. spinosum, Glacilaria salicornia, Hypnea nidulans, Galaxaura apiculata. The results of the analysis of the width of the recesses showed that the macro algae species with the largest recess width were Eucheuma denticulatum with a value of 0.905, while Galaxura apiculata had the narrowest recess widths with a value of 0.200. Furthermore, based on the results of overlapping analysis of microhabitat niches, it shows that the overlap of microbaitate niches is quite large by Sargassum polycestum against Galaxaura apiculata with a value of 0.337, while the lowest was carried out by Halimeda macroloba against Galaxaura apiculata, Halimeda opuntia forma chordata against Galaxaura apiculata with a value of 0.337, while the lowest was carried out by Halimeda macroloba against Galaxaura apiculata, Halimeda opuntia forma chordata against Galaxaura apiculata, Eucheuma spinosum against Galaxaura apiculata with a value of 0.000.